Tomáškovy dny 2021 XXX. konference mladých mikrobiologů - Vacek, Lukáš; Kleknerová, Dominika (Masaryk University Press, 2021)
Title in English: Tomasek Days 2021: XXX. Conference of Young Microbiologists. Tomasek Days of Young Microbiologists is a conference which has been organized since 1992 annually by the Department of Microbiology, Faculty of Medicine, Masaryk University in Brno and St. Anne's University Hospital in Brno in cooperation with Czechoslovak Society for Microbiology. The other official conference organizers are The Czech Medical Association J. E. Purkyně and the Society for Medical Microbiology CMA JEP. The presenting author (or main author of the poster) must be under 36 years old.